CAR RENTAL AND TRACKING WEB-BASED SYSTEM USING GPS - Osman A Nasr; Mohamed N Miladi; Mohammad Ahmed (STMIK Pringsewu Lampung, 2020)
A car rental is a process to allow use car temporarily for a period with a fee renting, with technology customers need to reduce the time and effort in obtaining their needs, and we find that some customers who stay for temporary periods in places other than where they live have a desire to get a car for rent. Through this research will develop an electronic web-based system to provide a service Car rental for customers as well as the possibility of managing car rental agencies for the owner. This system will present a excellent tools tool for fast and accurate development of car rental service. Agile methodology and WebML methodology relied upon to carry out the search. The electronic web-based system application will allow improvement and quality of services provided to clients who have the desire to get a car for rent, and the car rental agencies that offer car rental services, and also the electronic system provides monitoring of cars that will be rented through the GPS service, which facilitates the process of controlling rental cars, Also some electronic system components will be added and reused.